Effective teaching of secondary school mathematics through mastery learning strategy (2011)
Over the years, mathematics had been a most dreadful subject at all levels of education. The phobia students have for the subject might not be unconnected with the teaching strategies which the subject teachers have been using. This paper attempted to present Mastery Learning Strategy (MLS) as a strategy that teachers can use to assist learners to learn mathematics. Recommendations on how to overcome envisaged problems while using the strategy and how to adapt the strategy for usage were given